Infecção do trato urinário em pacientes idosos com incontinência urinária: um estudo de coorte - Lais Samara de Melo (2016)
The Urinary incontinence is a complaint of any involuntary loss of urine; it is common condition in general population increasing prevalence with the advancing age. Studies have shown the presence of this disorder as a risk factor for the occurrence of urinary tract infections in the elderly population. However, the mechanisms which urinary incontinence contributes to the occurrence are not well describe in literature. Urinary infections are one of the most frequent infections in elderly living in home nurse care, with an impact on increasing the number of hospital admissions, morbidity and mortality of elderly patients. The grown number of elderly people in the country and the consequences of urinary tract infections in this population, this study becomes relevant to analyze the incidence of urinary tract infections in elderly people who have urinary incontinence, as well as risk factors for the development this problem. The aim of the study was to evaluate the incidence and risk factors for urinary tract infections in elderly patients with urinary incontinence, residents in a Home Nurse care at Belo Horizonte. This is a concurrent cohort conducted from April to October 2015. The study was conduct in two Home Nurse care in the city of Belo Horizonte, MG, with 84 incontinent elderly. Before the data collection, researchers who collaborated with the study, were training and submit to an evaluation of agreement among them. The data collection had four steps: medical record data collection, scale application to determine the degree of functional dependence, diaper weight and average number of diapering in 24hrs and monitoring of patients between on 01 April to 01 October 2015, to determine the incidence of UTI during the study period. The descriptive analysis was made by the used of measures of central tendency and variability. Then the bivariate analysis was performed. To identify the independent variables associated with the UTI was performed logistic regression based on forward stepwise method. The cumulative incidence of UTI was 19% (95% CI: 7.83 to 23.19) and DI calculated was 3.6 cases / 100 person-months of follow-up. The bacteriuria variables and institution were associated with the occurrence of urinary tract infection. It is observed that the incidence of UTI in the study was lower than in similar studies, however it is a major health problem for the elderly, with an impact on mortality of these individuals.